3D Printing of a Flexible Inclined‐Tip Cone Array‐Based Pressure Sensor. Issue 6 (22nd December 2021) - Li, Tong; Pan, Peng; Yang, Zhengchun; Wei, Jun; Yang, Xiaoping; Liu, Jun; Zhou, Jie; Zhang, Xiaodong; Liu, Guanying
Abstract: The high sensitivity and portability of flexible pressure sensors have attracted widespread attention from researchers owing to their potential use in health monitoring and exercise detection applications. However, to improve the performance of pressure sensors, a special microstructure‐shaped design is necessary, which usually requires a complicated manufacturing process. In this study, the use of 3D printing technology is proposed to develop a polydimethylsiloxane‐based material along with several conductive materials—carbon black, multiwalled carbon nanotubes, and copper mixed conductive ink—to develop a multilevel inclined‐tip cone array structure to obtain a flexible pressure sensor with a wide detection range and high sensitivity. The final pressure sensor demonstrates a wide range of 0–396 kPa, achieving a high sensitivity of 212 kPa −1, a response time of 32 ms, a low detection limit of 7.69 Pa, along with high stability and consistency under a 5000 cycles compression test. 3D printing technology is used directly in the manufacturing process to achieve low‐cost production. The pressure sensor can accurately identify finger, arm (bending), and leg (jumping) movements, along with the detection of pulse waves. It has opened up new test methods for pulse diagnosis in traditional Chinese medicine and has far‐reaching research significance. Abstract : 3D printing technology is used to develop a multilevel structure of tilted cone array on polydimethylsiloxane/carbon black/multiwalled carbon nanotubes/Cu‐mixed conductive ink to obtain a pressure sensor with detection range (0–396 kPa) and high sensitivity of 212 kPa −1 . Using the tension method to test the pulse signal for traditional Chinese medicine diagnosis.